A case of metastasis of small cell lung cancer to the parotid gland: a case report and literature review. Issue 11 (November 2019) - Cui, Yu; Cui, Xiang-Yan; Wu, Yu; Yin, Wan-Zhong; Zhu, Zhan-Peng
Small cell lung cancer metastasizing to the parotid gland is very rare and only a few cases have been reported. A 64-year-old man presented with a painless mass and peripheral facial paralysis. Neck ultrasound identified a solid mass in the right parotid gland with enlargement of the lymph nodes in the gland and the right submandibular lymph nodes. Lung computed tomography imaging demonstrated abnormalities in the upper and middle lobes of the right lung and intermediate bronchus, with obstructive pneumonia, as well as enlargement of the right hilar and mediastinal lymph nodes. Postoperative histopathological analysis identified small cell carcinoma in the right parotid gland with involvement of the right neck lymph nodes (one of eight). Bronchoscopy was performed and immunohistochemical analysis of the specimen demonstrated possible metastasis of small cell lung cancer to the parotid gland. From postoperative day 15, the patient started to undergo six cycles of an adjuvant chemotherapy regimen. No complications of the chemotherapy regimen were observed after three cycles. Treatment and follow-up are ongoing.